Impact of Aging on the Phenotype of Invariant Natural Killer T Cells in Mouse Thymus - Papadogianni, Georgia; Ravens, Inga; Dittrich-Breiholz, Oliver; Bernhardt, Günter; Georgiev, Hristo (Frontiers in Immunology, 2020)
Invariant natural killer T (iNKT) cells represent a subclass of T cells possessing a restricted repertoire of T cell receptors enabling them to recognize lipid derived ligands. iNKT cells are continuously generated in thymus and differentiate into three main subpopulations: iNKT1, iNKT2 and iNKT17 cells. We investigated the transcriptomes of these subsets comparing cells isolated from young adult (6-10 weeks old) and aged BALB/c mice (25-30 weeks of age) in order to identify genes subject to an age-related regulation of expression. These time points were selected to take into consideration the consequences of thymic involution that radically alter the existing micro-milieu. Significant differences were detected in the expression of histone genes affecting all iNKT subclasses. Also the proliferative capacity of iNKT cells decreased substantially upon aging. Several genes were identified as possible candidates causing significant age-dependent changes in iNKT cell generation and/or function such as genes coding for granzyme A, ZO-1, EZH2, SOX4, IGF1 receptor, FLT4 and CD25. Moreover, we provide evidence that IL2 differentially affects homeostasis of iNKT subclasses with iNKT17 cells engaging a unique mechanism to respond to IL2 by initiating a slow rate of proliferation.